Legalitas dan Birokrasi dalam Pendirian Fasilitas Kesehatan serta Diskrepansi Regulasi dan Implikasi Yuridis bagi Investasi dan Akses Layanan Kesehatan di Indonesia - Natasya Dwi Nanda (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The licensing of clinics and hospitals is crucial for achieving quality and equitable healthcare in Indonesia. The legal framework, including the 2009 Health Law and the 2020 Omnibus Law, has introduced a risk-based approach via the Online Single Submission (OSS) system to streamline the process. However, significant challenges remain. These include bureaucratic complexity, inconsistent regional regulations due to autonomy, lack of data integration between institutions, and high accreditation costs. These barriers particularly hinder small investors and limit the distribution of healthcare facilities in remote areas. Recent reforms, such as the National Digital Public Service Mall (MPP Digital), aim to address these issues by reducing licensing time to under one hour, thereby boosting transparency and efficiency. Despite this progress, unresolved issues concerning patient data privacy, the uneven distribution of medical personnel, and conflicting environmental regulations still need harmonization. To foster inclusive investment and support the 2030 Universal Health Coverage (UHC) goals, this research proposes key solutions: implementing fiscal incentives, adopting AI technology for verification, and strengthening public-private partnerships. With these targeted reforms, the licensing system can become a powerful driver for better healthcare access and sectoral growth.